Obsessive-Compulsive Symptoms in an Adolescent with Intellectual Disability - Al-Abdullah, Zainab; Nawaz, Faisal A.; Kair, Hawk M.; Sultan, Meshal A. (Case Reports in Psychiatry, 2022)
Individuals with intellectual disability (ID) experience various psychiatric comorbidities including anxiety, depression, and obsessive-compulsive disorder (OCD) in a rate that is equivalent or higher than individuals without ID. Unfortunately, these cooccurring conditions are often missed during the evaluations due to various reasons, including their atypical presentation. In this case report, we present the clinical symptoms of an adolescent with mild ID who presented with irritability and was diagnosed with OCD following a comprehensive assessment. The treatment course is also summarized as well as the positive outcome to selective serotonin reuptake inhibitor (SSRI) medication. In this report, we discuss potential factors that increase the rate of psychiatric comorbidities including OCD in individuals with ID. Furthermore, in the context of limited research in this area, we recommend additional studies in order to build a detailed understanding of the clinical presentation of psychiatric cooccurring disorders in individuals with ID with the goal of enhancing assessment tools in the future.